PERANCANGAN SARANA PENYELAMAT DIRI DAN KEBUTUHAN APAR PADA DARURAT KEBAKARAN DI KANTOR KESEHATAN PELABUHAN KELAS II BALIKPAPAN - Agus Pratama (Universitas Airlangga, 2016)
Fire in building could cause human casualties, loss of property, disruption of the activities of the organization, environmental degradation and disturbance of public. In the United State, of 15.300 fire in the rise building are 990 victims and 6,1% of them fatalities. Therefore fire prevention should be done by implementing the emergency response system wherein fire extinguishing system and means of escape. The purpose of this study was to identify and designing needs portable fire extinguisher and means of escape that have not been fulfilled in building Class II Port Health Office (PHO) of Balikpapan. This research was performed by cross sectional design using observational approach. The interviews performed on 2 officials of Class II PHO of Balikpapan which is considered to know about the condition of the building as object of research. The result of this research are no fire emergency policy and means of escape. In these condition it is provided to the Class II PHO of Balikpapan fixed procedure on fire emergency and evacuation route. Portable fire extinguisher installed as many as 10 units, in accordance with the requirements calculated based Permenakertrans number 4 1980. Conclusion of this research is Class II PHO of Balikpapan’s building has not been having fire emergency policy and adequate means of escape. This condition should see the Class II PHO of Balikpapan create procedure regarding fire emergency and evacuation route.Keywords: fire emergency, means of escape, portable fire extinguisher